THE PRINCIPLE OF NON-PUNISHMENT FOR VICTIMS OF HUMAN TRAFFICKING – INTERNATIONAL LEGAL STANDARDS AND THE SITUATION IN THE REPUBLIC OF SERBIA - Turanjanin, Veljko; Jeličić, Mladen (Glasnik Advokatske komore Vojvodine, 2025)
The authors analyze the principle of non-punishment of victims of human trafficking through the prism of international legal standards in this area and the situation in the Republic of Serbia. After introductory remarks on the importance of this issue, the authors point to the international legal framework that follows the mentioned principle, but also to examples from comparative law, good judicial practice and decisions of the European Court of Human Rights. Considering that the application of this principle in practice implies the prior identification of the victim of human trafficking, this procedure in the Republic of Serbia is analyzed. Special attention is paid to the competences of the Center for the Protection of Victims of Human Trafficking, which is the only state body competent for the implementation of the mentioned procedure. Then, the authors considered the above issue from the perspective of the third GRETA report, and also pointed out the current steps taken by Serbia towards fulfilling its international obligations, and summarized the provisions of the Draft Law on Suppression and Prevention of Trafficking in Human Beings and Protection of Victims with regard to the principle of non-punishment. The authors conclude that the implementation of the principle of non-punishment of victims of trafficking in human beings into the positive legal system of the Republic of Serbia, in accordance with international standards, should be accompanied by appropriate amendments to the Criminal Code, the Code of Criminal Procedure and the Law on Misdemeanors.